International Consultation on Incontinence Questionnaire‐Satisfaction: psychometric testing of a new patient‐reported outcome measure for the evaluation of satisfaction after urological surgery. (20th May 2020) - Uren, Alan D.; Cotterill, Nikki; Hashim, Hashim; Worthington, Jo; Kapoor, Dharmesh; Abrams, Paul
Abstract : Objectives: To evaluate the psychometric properties of a new patient‐reported outcome measure (PROM), the International Consultation on Incontinence Questionnaire‐Satisfaction (ICIQ‐S), to assess satisfaction after urological surgery. Subjects/Patients and Methods: Following item development, the developmental ICIQ‐S (dICIQ‐S) was used within in a randomised control trial comparing two types of surgery for male prostatic obstruction at 1.5, 3, and 12 months after surgery. Reliability was assessed by Cronbach's α and construct validity by the correlation of scores with concurrently administered PROMs of known validity: ICIQ‐Male Lower Urinary Tract Symptoms (LUTS), International Prostate Symptom Score, and the ICIQ‐LUTS Quality of Life. Results: A total of 410 men were included in the trial. Missing data was generally low for the dICIQ‐S [mean (range) 1.6 (<1–3.1)%] except for the items 'complications' 6.8% and 'satisfaction with sex‐life' 9.2%. High ceiling effects were found in all items. Factor analysis identified six items related to surgical outcomes (Cronbach's α 0.89), which have formed the scored part of the ICIQ‐S, together with a standalone overall satisfaction item, scored 0–10. Seven additional unscored items, related to satisfaction with experiences and expectations, were also retained. As hypothesised, post‐surgery dICIQ‐S scores were correlated with reduced symptoms and improved quality of life as measured by the concurrent PROMs. Conclusion: The results support the validity and reliability of a scored six‐item domain for evaluating satisfaction with surgical outcomes, together with a standalone scored overall satisfaction item. The further unscored seven standalone items are anticipated to be used as the basis for adaptation and further validation of the ICIQ‐S in different patient populations.